Antioxidant and polyphenol activity of Piper sp extracts. "matico" collected in the district of Levanto, Amazonas - Alvarado Santillán, Gingler (2020)
The objective of the research was to determine the antioxidant activity and phenols of matico extracts (Piper sp.) At different altitudes in the district of Levanto, Amazonas. For this, three types of extracts (aqueous, ethanolic and methanolic) were obtained from leaves collected at three different altitudes; Then, the antioxidant activity was determined using the DPPH technique (uptake of the free radical 2,2-diphenyl-1-picrylhydrazyl) and quantified the total polyphenols using the Folin Ciocalteu technique. Significant differences (sig. = 0.05) were found in the altitude and the type of extract; evidencing that higher altitude increased antioxidant activity and the best extract was the aqueous extract against alcoholic extracts.